Reconsidering the origins of isotopic variations in Ocean Island Basalts: Insights from fine-scale study of São Jorge Island, Azores archipelago - Millet, Marc-Alban; Doucelance, Régis; Baker, Joel A.; Schiano, Pierre (Chemical Geology, 2009)
New major and trace element and Sr–Nd–Pb isotope data have been determined for 21 basaltic samples from São Jorge Island, Azores archipelago. Samples can be separated into two groups best identified in a plot of 208Pb/204Pb versus 206Pb/204Pb where they form two sub-parallel mixing arrays. Lavas from the old (Topo) formation have lower 208Pb/204Pb for a given 206Pb/204Pb and more radiogenic Sr than samples from intermediate (Rosais) and young (Manadas) formations. Topo samples also tend to have higher MgO contents and lower incompatible trace element concentrations. Both Pb mixing arrays can be related to mixing of plume melts having a HIMU-like Pb isotope signature with two depleted components. One depleted component is best seen in analyses of Topo samples and is interpreted to represent upper mantle material from the nearby Mid-Atlantic ridge. The second depleted component has Sr–Nd–Pb isotopic characteristics similar to E-MORB and resides in the oceanic crust basement under São Jorge. Pb isotope analyses of lavas from São Jorge make it possible to re-define the Terceira end-member of the Azores archipelago, moving its composition to more radiogenic Pb with 206Pb/204Pb ~ 20.51, 207Pb/204Pb ~ 15.67 and 208Pb/204Pb ~ 39.56, at 143Nd/144Nd ~ 0.51295 and 87Sr/86Sr ~ 0.70375. Extending the interpretations made for the origins of the São Jorge isotopic mixing arrays to other islands from the Azores archipelago (Pico, Faial, Terceira and São Miguel), we show that most of the isotopic variability recorded by Azores magmas can be related to mixing of plume melts with two distinct and homogeneous signatures as well as several other components dispersed in the shallow mantle/lithosphere under the Azores. This illustrates how caution is required when interpreting ocean island basalt isotopic data as reflecting their deep mantle plume source, and subsequently for constraining mantle topology.